ANALISIS PENDAPATAN DAN KELAYAKAN USAHA JAMUR TIRAM PUTIH DI MURI JAMUR KUPANG - Mbuik, Wili; Kapa, Maximillian M.J.; Un, Paulus; Pellokila, Marthen R. (Undana Press, 2023)
The white oyster mushroom business can be said to be successful if the business can provide optimal results. Optimal results are determined from the income earned and the feasibility level of the business being run. This study aims to determine the Revenue and Feasibility of the White Oyster Mushroom Business in the Kupang Mushroom Muri Business. The research location is at the Kupang Mushroom Muri Business which was determined intentionally (purposive sampling). Data analysis was carried out using the Quantitative Method, namely income analysis, and financial feasibility which was analyzed using the investment criteria analysis method. The results of this study show that the income earned by the owner of the White Oyster Mushroom Business in 2022 is Rp. 68,242,952. The results of the financial feasibility analysis show an NPV value of Rp.329,854,793, Net B/C of 5, IRR of 23%, and Payback Period of 1 year and 7 months. From the results of this analysis it is known that the White Oyster Mushroom Business at Muri Mushroom Kupang is feasible to cultivate.